Izzy's Tail of Trouble - Adderson, Caroline, 1963-; Collier, Kelly (Toronto, ON : Kids Can Press, 2022)
c
580L
Decoding demand: 83 (very high)
Semantic demand: 94 (very high)
Syntactic demand: 83 (very high)
Structure demand: 85 (very high)
Keywords: Puppies -- Juvenile fiction; Siblings -- Juvenile fiction; Sibling rivalry -- Juvenile fiction; Families -- Juvenile fiction; Dogs -- Juvenile fiction; Girls -- Juvenile fiction; Best friends -- Juvenile fiction; Teenagers -- Juvenile fiction